Self-Assessment by Self-Questioning in the Instructional and Practical Phases of Mathematics Learning - Mastnak, Adrijana; Valenčič Zuljan, Milena; Magajna, Zlatan (Pedagogika, 2023)
In this paper, we present a study in which we developed a self-assessment model based on students’ self-questioning, and investigated its impact on improving the accuracy of students’ self-assessment. The impact of the model was determined on a sample of 164 Grade 7 students in the instructional and practical phases of mathematics learning. It was found that the use of the model resulted in improved accuracy in students’ self-assessment in both phases and, for low- and high- achievers.